Cardiovascular risk behavior among students of a Medical College in Delhi - N Rustagi; D K Taneja; P Mishra; G K Ingle (Wolters Kluwer Medknow Publications, 2011)
Background: Life style related behavioural risk factors are mainly implicated for increased burden of cardio- vascular diseases. Research related to these risk behaviours especially among medical students is essential, considering their role as future physicians and role models in public health intervention programmes. Objective: To evaluate the burden of cardiovascular risk behaviours among students of a medical college of Delhi, India. Materials and Methods: A cross sectional study was carried out among undergraduate medical students of a medical college in Delhi. Self administered questionnaire was used to collect information on identification data and risk behaviours in relation to cardiovascular diseases. Binary logistic regression analysis was done to calculate adjusted odds ratio to assess association between risk behaviours and covariates. Results: The minimum recommendation of taking at least five servings per day of fruits and vegetables was complied only by 12% of students. Consumption of carbonated soft drinks either once or more on daily basis was present in 23.7% students and 32.0% reported frequent consumption of fast foods in past week. Consumption of alcohol was present in 28.8% students but only small proportion of students (7%) was current tobacco users. Large proportions of students (42.6%) were either not carrying out or were involved in only occasional physical activity in past week. Conclusions: Unhealthy behavioural practises are present and may progress as student advance through medical college. Developing strategies targeting at these risk behaviours and determining factors is necessary to promote healthy life style among medical students.